A cultural comparison of children’s emotion knowledge: Data from two cultures - Schapira, Rotem; Salisch, Maria von; Voltmer, Katharina (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Knowing about emotions is vital for children’s school adjustment, well-being, and future social relationships. Whereas experiencing emotions is a universal psychological process at the biological level, how emotions are categorized and communicated is shaped by culture. Most studies have investigated cultural differences in emotion (knowledge) in Western and Eastern cultures. To compare emotion knowledge within Western countries, N  = 585 children from Germany and N  = 100 children from Israel in the two age groups preschool (42–71 months) and primary school (72–89 months) were interviewed with the Adaptive Test of Emotion Knowledge for Three- to Nine-Year-Olds (ATEM 3-9). Generalized linear models (GLMs) indicate that children from Israel showed higher levels of emotion knowledge in the total score and in all seven components of emotion knowledge than their agemates from Germany. These results highlight the importance of differences in family structure and values within Western countries. It is important to determine the various factors and the socialization in the family and in educational institutions that influence emotion knowledge in Germany and Israel.
Keywords: Emotion Knowledge; Emotional Competence; Cultural Difference; Preschool; School-age Children